KUALITAS BUAH STROBERI TOMOHON - Bertje R.A. Sumayku; Meity N. Tanor (Universitas Sam Ratulangi, 2022)
This study aims to decomposers effectiveness of Trichoderma koningii against Strawberry fruit quality. This study was conducted in screen house, in the Rurukan Village, Eastern District of Tomohon. Strawberry fruit quality analysis conducted in Laboratarium Technology of Faculty of Agriculture Unsrat Manado. The study was conducted in a completely randomized design. Treatment dose T. koningii in manure and organic potash (ash coconut), as follows: TO = 0 T. koningii g / kg of soil; P1 = 0 g T.koningii / kg soil + Manure 5 ton / ha + Abu Kelapa 400 kg / ha; T.koningii P2 = 5 g / kg soil + Manure 5 ton / ha + Abu Kelapa 400 kg / ha; T.koningii P3 = 10 g / kg soil + Manure 5 ton / ha + Abu Kelapa 400 kg / ha and T.koningii P4 = 15 g / kg soil + Manure 5 ton / ha + Abu Kelapa 400 kg / ha, the treatment is repeated 3 times. The observed variables include: fruit color, texture of the fruit, sugar and vitamin C content of strawberries. Data were analyzed by analysis of variance, followed by Duncan test Î± 0.05. The results showed that utilization of T. koningii as decomposers can improve the quality of Strawberries in Tomohon, for variable: violence fruit, sugar and vitamin C content of strawberries. T.koningii effective dose on the sugar content of strawberries, is the treatment of P4 with sugar content of 11.0%, and the Vitamin C content of 40 623 mg / 100 g.